Case series: Interstitial lung disease with IPF pattern presenting with spontaneous pneumothorax—clinical course of two patients - Toshniwal, Amit; Ghewade, Babaji; Jain, Alushika; Toshniwal, Saket Satyasham (Frontiers in Medicine, 2025)
BackgroundInterstitial lung disease (ILD) encompasses a broad spectrum of fibrosing pulmonary conditions. Pneumothorax is a recognized complication of fibrotic ILD, but simultaneous occurrence with subcutaneous emphysema and pneumomediastinum is exceedingly rare.Case presentationThis case series describes two patients with idiopathic pulmonary fibrosis (IPF)-pattern ILD who experienced complications from spontaneous pneumothorax. In the first case, the patient arrived at the emergency department with worsening shortness of breath. Imaging revealed the presence of spontaneous pneumothorax, pneumomediastinum, and subcutaneous emphysema. The patient’s condition deteriorated rapidly and ultimately succumbed to respiratory failure. The second case involved a female patient who initially presented with chronic respiratory symptoms and was later diagnosed with probable usual interstitial pneumonia (UIP)-pattern ILD. During the follow-up, she exhibited worsening symptoms and was diagnosed with a spontaneous pneumothorax, which was treated successfully with conservative management.ConclusionTo the best of our knowledge, this is the first reported case series that document the triad of subcutaneous emphysema, pneumomediastinum, and pneumothorax in a patient with fibrotic ILD. The findings underscore the importance of timely recognition and multidisciplinary management for such high-risk patients.